FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDINGS PADA PERUSAHAAN PELAYARAN DI INDONESIA - Zulyani Zulyani; Hardiyanto Hardiyanto (Politeknik Negeri Bengkalis, 2019)
The purpose of this study was to examine determinants the factors that influence cash holdings on shipping companies listed on the Indonesia Stock Exchange from 2015 to 2017. The study sample used quarterly financial performance for 12 shipping companies. This study uses a fixed effect model. The results revealed that net working capital had a significant positive effect on cash holding in shipping companies in Indonesia, while cash flow, cash flow variability, liquidity, leverage and firm size did not significantly influence to cash holdings.